New donor-functionalized cp ligands: synthesis and complexation behaviour of quinoxalyl and benzothiadiazolyl systems - Schuhen, Katrin; Sieb, David; Wadepohl, Hubert; Enders, Markus (Zeitschrift für anorganische und allgemeine Chemie, 2009)
Sodium cyclopentadienide reacts as nucleophile with 4,7-dibromo-2,1,3-benzothiadiazole (BTZ) and leads to the new donor-functionalized ligand CpBTZ. Related quinoxalyl Cp systems have been prepared using Pd-catalyzed coupling with zincated Cp-metal complexes. The new ligands comprise two N-donor atoms; one of them is located in a distal position relative to the metal centre so that it cannotcoordinate in a chelating manner. With CpBTZ ligand derivatives severalmetal complexes have been synthesized. The new chromium(III) complex CpBTZCrCl2 (12) becomes upon activation an active catalyst for the polymerization of ethylene. Relying on DFT calculations and analysis of spin-density distribution combined with paramagnetic NMR data a chelating coordination of the CpBTZ ligand is feasible in 12.